The bright homunculus in our head: Individual differences in intuitive sensitivity to logical validity. Issue 3 (March 2022) - Ghasemi, Omid; Handley, Simon; Howarth, Stephanie
Classic dual process theories of human reasoning attribute explicit reasoning to effortful, deliberative thinking. According to these models, intuitive processes lack any access to the formal rules of logic and probability and hence rely exclusively on superficial problem features to determine a response. However, in recent years, researchers have demonstrated that reasoners are able to solve simple logical or probabilistic problems relatively automatically, a capability which has been called "logical intuition." In four experiments, we instructed participants to judge the validity (Experiments 1 and 4), likeability (Experiments 1, 2, and 3), and physical brightness (Experiments 2, 3, and 4) of the conclusion to several reasoning problems. Brightness judgements were made by evaluating the font shade brightness of the argument's conclusion. Participants were also asked to complete a range of individual differences measures, drawing on cognitive ability and cognitive style, to evaluate the extent to which "logical intuitions" were linked to measures of deliberative reasoning. The results showed that participants judged the conclusion of logically valid statements to be more valid, more likable, and more physically bright than invalid statements. Participants with higher cognitive ability and unlimited processing time showed greater effects of logical validity in their liking judgements (varied across experiments). However, these effects were absent in the brightness tasks, suggesting that logic effects observed under instructions to judge conclusion brightness are a purer measure of "logical intuition." We discuss the implications of our findings for recent dual process theories of human reasoning.